Immediate Effects of two Isometric Calf Muscle Exercises on Mid-portion Achilles Tendon Pain - Bradford, Ben; Rio, Ebonie; Murphy, Myles; Wells, Jacob; Khondoker, Mizanur; Clarke, Celia; Chan, York; Chester, Rachel (International Journal of Sports Medicine, 2021)
The objectives of this randomized, cross-over pilot study were to determine whether isometric plantarflexion exercises resulted in an immediate change in Achilles tendon pain during a loading task, and whether this differed in knee extension or flexion. Eleven participants with mid-portion Achilles tendinopathy were recruited from NHS community physiotherapy services and local running clubs. Participants were then randomized to complete an isometric calf muscle exercise with the knee fully extended or flexed to 80°. Participants switched to the alternate exercise after a minimum seven-day period. Achilles tendon pain during a specific, functional load test was measured on a 11-point numeric pain rating scale (NPRS) pre- and post-intervention. There was a small, immediate, mean reduction in pain following isometric plantar flexion performed in both knee extension (1.6, 95%CI 0.83 to 2.45, p=0.001) and knee flexion (1.3, 95%CI 0.31 to 2.19, p=0.015). There were no significant differences between the two positions. A non-significant, potentially clinically relevant finding was a 20% larger reduction in symptoms in knee extension versus flexion (p=0.110). In conclusion, isometric plantarflexion holds gave an approximately 50% immediate reduction in Achilles tendon pain with a functional load test. There were no significant differences between the two positions and both were well tolerated.
Keywords: tendinopathy; physiotherapy; exercise; pain